2018
DOI: 10.1259/bjr.20180317
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the validity of utilising the CDRAD 2.0 phantom for optimisation studies in digital radiography

Abstract: Objectives: To determine if a relationship exists between low contrast detail (LCD) detectability using the CDRAD 2.0 phantom, visual measures of image quality (IQ) and simulated lesion visibility (LV) when performing digital chest radiography (CXR). Methods: Using a range of acquisition parameters, a CDRAD 2.0 phantom was used to acquire a set of images with different levels of image quality. LCD detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…De Crop et al [16]. More recently, a study undertaken by our research group confirmed the validity of physical evaluation for LCD detectability using CDRAD 2.0 phantom for evaluating visual IQ and lesion visibility along with its validity in CXR optimisation studies [36]. Within this work it was concluded that there is a good correlation between the LCD detectability and the visibility of the lesions and the general visual IQ within CXR.…”
Section: Discussionsupporting
confidence: 66%
“…De Crop et al [16]. More recently, a study undertaken by our research group confirmed the validity of physical evaluation for LCD detectability using CDRAD 2.0 phantom for evaluating visual IQ and lesion visibility along with its validity in CXR optimisation studies [36]. Within this work it was concluded that there is a good correlation between the LCD detectability and the visibility of the lesions and the general visual IQ within CXR.…”
Section: Discussionsupporting
confidence: 66%
“…Implementation of the VGA method is not feasible within a routine quality assurance program because it requires a substantial additional workload for the radiologists and large patient numbers or phantom images. 10,16,18 The psychophysical measurements based on CD images analysis are more practical than VGA method because no patient data are required and images can be analyzed by the medical physicist or dedicated image analyzer software. The eDQE measurement technique is a new metric when compared with VGA and CD analysis methods and provides overall performance of the digital radiographic imaging system in clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For the determination of the correlation between ordinal data (e.g., Likert scale) and continuous (interval) data Spearman correlation method was suggested in other studies. 10,18,32 Therefore, we used this statistical method to determine the correlation between VGA score (ordinal data), IQFinv and IeDQE (continuous data), respectively. But Keeble et al have demonstrated that this should not be the way to analyze correlations between VGA (noncontinuous) and numerical metrics (continuous) and there is considerable debate within the statistics community on this subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, a quantitative assessment was conducted using accepted methodology. Images of the internationally recognised "CDRAD" contrast and detail phantom (Al-Murshedi, et al, 2018) were collected on both a standard system and the Trueview software and the processed images assessed by the included software to quantify performance. Images were taken on the standard system both with and without an ASG present to highlight the negative effect of scatter on the image.…”
Section: Scatter Corrected Image Qualitymentioning
confidence: 99%